Mouth opening and trismus in patients undergoing curative treatment for head and neck cancer. Issue 3 (March 2015) - Steiner, F.; Evans, J.; Marsh, R.; Rigby, P.; James, S.; Sutherland, K.; Wickens, R.; Nedev, N.; Kelly, B.; Tan, S.T.
Abstract This study documents mouth opening and the incidence of and factors contributing to trismus (<35 mm mouth opening), as well as the associated impact on quality of life, following curative treatment for head and neck cancer. Patient demographics, cancer type and location, and treatments were documented. Mouth opening was measured at >6 months after treatment completion. Patients rated the impact of mouth opening on quality of life from 0 (no effect) to 10 (greatest effect). The mean mouth opening in 120 patients was 40.1 mm (range 11–65 mm), with trismus occurring in 34 (28.3%) patients. Surgery and radiotherapy, surgery and chemoradiotherapy, and resection and reconstruction were associated with reduced mouth opening. The mean effect of mouth opening on quality of life for those with and without trismus was 3.8 and 1.5, respectively. There was a significant difference between the mean effect on quality of life for patients with and without trismus for those patients who underwent chemoradiotherapy or combined surgery and radiotherapy (4.0 vs. 1.0, and 3.6 vs. 1.6 respectively). Trismus impacts negatively on patient quality of life. Multi-modality treatment is associated with decreased mouth opening, an increased incidence of trismus, and reduced quality of life.